A replication study of 49 Type 2 diabetes risk variants in a Punjabi Pakistani population. Issue 8 (12th December 2015) - Zia, A.; Wang, X.; Bhatti, A.; Demirci, F. Y.; Zhao, W.; Rasheed, A.; Samuel, M.; Kiani, A. K.; Ismail, M.; Zafar, J.; John, P.; Saleheen, D.; et al.
Abstract: Aim: The burden of Type 2 diabetes is alarmingly high in South Asia, a region that has many genetically diverse ethnic populations. Genome‐wide association studies (GWAS) conducted largely in European populations have identified a number of loci predisposing to Type 2 diabetes risk, however, the relevance of such genetic loci in many South Asian sub‐ethnicities remains elusive. The aim of this study was to replicate 49 single nucleotide polymorphisms (SNPs) previously identified through GWAS in Punjabis living in Pakistan. Methods: We examined the association of 49 SNPs in 853 Type 2 diabetes cases and 1945 controls using additive logistic regression models after adjusting for age and gender. Results: Of the 49 SNPs investigated, eight showed a nominal association ( P < 0.05) that also remained significant after controlling for the false discovery rate. The most significant association was found for rs7903146 at the TCF7L2 locus. For a per unit increase in the risk score comprising of all the 49 SNPs, the odds ratio in association with Type 2 diabetes risk was 1.16 (95% CI 1.13–1.19, P < 2.0E–16). Conclusion: These results suggest that some Type 2 diabetes susceptibility loci are shared between Europeans and Punjabis living in Pakistan. What's new?: There have been limited studies on the genetic basis of Type 2 diabetes in the Pakistani population. This study aimed to replicate 49 genome‐wide association studies significant single nucleotide polymorphisms in a Pakistani Punjabi population. Eight single nucleotide polymorphisms showed a strong association with Type 2 diabetes in the Pakistani population. This highlights the existence and importance of sub‐population heterogeneity. An association with an alternate allele for KCNQ1 and KLF14 genes was identified.